O financiamento privado da Inovação Biofarmacêutica no Brasil: uma proposta - Ricardo Jose Ferreira Rodarte (2015)
Pharmaceutical Industry occupies an envied prominent position when compared to other sectors of global economy. This position is due not only to the innovation and quality of its products, but also to the volume of investments in R&D&I, the huge sums of money involved in its business and the high profit margins. Behind this reality, there is the dynamic sector of biopharmaceutical innovation, which uses its prominent role and the private investments received to contribute to the technological and commercial development of the global Pharmaceutical Industry. The industry of biopharmaceutical innovation is a relatively young segment that gained the investors attention due to its dynamics and the trend of great pharmaceutical corporations to outsource its projects of R&D. In Brazil, the Pharmaceutical industry currently finds itself within a reality which, in spite of the various Governmental stimulus and support to all levels of research, development and innovation, the country has not been able to transform the result of this efforts into economic growth, better innovation indexes of its industrial facilities and better results in its trade balance. Unfortunately, Brazil is still seen in the international arena as an usual importer of technologies. In order to revert this status, it is necessary to overcome several setbacks, including certain cultural aspects that maintain the gap between the corporations and the academia, the presence of an unfavorable regulatory and business environment and the lack of a continuous and sustainable model of private funding focused on the R&D&I activities connected to the Pharmaceutical segment. In view of the above, the current work presents an investments platform directed to acquisition of interest participation in companies specialized in Biopharmaceutical Innovation in Brazil, subject to the rules of the Brazilian Securities Exchange Commission. The to the sector, by introducing analytical tools such as the Success Indicators (SI) and methodologies such as the theory of Real Option (TOR) and the Adjusted Net Present Value (VLPr) that assist the investors' decision making process. platform aims at mitigating risks and attracting private investments